ANALYSIS OF THE RELATIONSHIP BETWEEN WELLBORE STABILITY AND OVERPRESSURE ZONE IN TANGGULANGIN AREA, NORTHEAST JAVA BASIN - SARMANTUA SITINJAK (NIM: 22012306), ERI
Tanggulangin oil and gas field located in Northeast Java Basin, one of the important operation areas in East Java, was firstly explored through drilling operation in 2001, and it has already produced significant oil and gas for PT.Lapindo Brantas. Therefore it is needed to optimize the production in Tanggulangin field through additional drilling or detailed geologic and geophysics analysies. The area of this thesis is Tanggulangin, Wunut, Banjar Panji and Porong, which has already known as an overpressured area. Five wells had been executed since 2001 in Tanggulangin and left so many problems and lesson learned that need to be investigated in order to do additional drilling operation. Some of the problems were gas kick, stuck pipe, mud losses, sloughing shale, overpull, tight section, ballooning effect, and mud flowing, which are very common in an overpressured area. If all these problems are not alerted and solved, they can guide to a major accident called blowout. Blowout is a fluid release event from a well after pressure knobs are not working properly or is a process of uncontrolled fluid event from the formation into the well. Blowout can be caused by overpressure condition that is defined as a condition where the pressure is higher than hydrostatic. The overpressure is caused by inability of the fluid in the formation to escape in response to overburden increment. Wellbore stability is the problem of all deviated and horizontal wells in the area that has very pressurized formation, like undercompacted sandstone, shale, and weak carbonates. Instability of the well can be started by simple enlargement of the diameter of the well to a formation rupture in the well. This problem is related to mechanic properties (strength and deformation processes under influence of pressure), property of the mud, in-situ stress field, and the length of the ongoing deformation. This thesis also covers geomechanics analysis to be used to analyse borehole stability. The development of overpressure model is based on Eaton method using petrophysical log from the wells and also from seismic interval velocity. Analysis shows that there is strong relationship and correlation between resulted overpressure zone from petrophysical logs and from seismic data. So it is reasonable to use seismic data to determine the overpressure zone in the deeper interval. Geomechanic model is an integrated study among stress, pore pressure, rock physics and fluid physics, structures from regional geology or seismic cross section, cap rocks and source rocks, and formations above the targeted reservoir. The geomechanic parameters are vertical stress (Sv), pore pressure (Pp), minimum horizontal stress (Shmin), maximum horizontal stress (SHmax) and rock strength, which are used to define the tectonic regime of Tanggulangin field. The direction of horizontal stress will be obtained from breakout or tensile features in resistivity image data. The direction of the horizontal stress and tectonic regime will be usefull in determining the optimum direction of future deviated or horizontal wells in Tanggulangin field in order to minimize wellbore stability problem in the wells. The tectonic regime in Tanggulangin field is strike slip-reverse regime, which has 900 - 1100 of Shmin direction. Drilling vertical well will be less stable than deviated and drilling to SHmax direction will be more stable for deviated or horizontal wells. The results of overpressure model from seismic interval velocity in seismic cross section (2D or 3D) shows several features like mud volcano which are intersected by some of the wells. Wells that intersected the overpressure zone (WNT-2, BJP-1, PRG-1) encountered significant wellbore stability problem. Wells that did not intersect the overpressure zone relatively more stable and have minimum wellbore stability problem. This thesis concludes that overpressure zone and wellbore stability are strongly correlated and connected to each other.